Giloe (Tinospora cordifolia) and Cinnamon (Cinnamomum zeylanicum) Powder Supplementation Effect on Growth Performance in Vencobb Broilers - Tiwari, Garima; Rahal, Anshu (International Journal of Bio-resource and Stress Management, 2026)
This experiment was conducted during month of December, 2016 to January, 2017 for 42 days at the Instructional Poultry Farm, Nagla, to evaluate the effect of Giloe and Cinnamon powder supplementation on growth performance, feed consumption (FC) and feed conversion ratio of Vencobb broiler chicken. Total one hundred twenty day old broilers chicks were procured and randomly divided into six treatment groups. While T1 was taken as control consisting of basal diet, T2, T3, T4, T5 and T6 basal diet were supplemented with 1% Giloe, 2% Giloe, 1% Cinnamon, 2% Cinnamon and a combination of 1% Giloe and 1% Cinnamon, respectively. During starter phase (0–21 days), the body weight gain was significantly (p≤0.05) higher in treatment group incorporated with 2% Giloe. The feed conversion ratio was significantly (p≤0.05) improved in broiler chicks fed diet incorporated with 1% Giloe. The performance index was significantly better in groups supplemented with 1% or 2% giloe. During finisher phase (22–42 days), the feed conversion ratio was significantly better in group supplemented with 1% Giloe with/without 1% Cinnamon . Performance index was significantly higher in group supplemented with 1% Giloe. During the whole experimental period (0–42 days), incorporation of 1% Giloe improved broiler performance in terms of body weight, weight gain, feed conversion ratio and performance index. Overall values indicated that 1% Giloe dietary incorporation can affect body weight and feed conversion ratio. Giloe @ 1% with/without Cinnamon can be fed in the broiler diet.